Immunohistopathological response against anisakid nematode larvae and a coccidian in Micromesistius poutassou from NE Atlantic waters. (10th March 2021) - Sayyaf Dezfuli, B.; Simoni, E.; Bosi, G.; Palomba, M.; Mattiucci, S.; Giulietti, L.; Bao, M.; Levsen, A.; Cipriani, P.
Abstract: A survey on Anisakis simplex ( sensu stricto ( s.s. )) from blue whiting, Micromesistius poutassou, in the north-eastern Atlantic Ocean revealed the occurrence of high infection levels of third larval stages in visceral organs and flesh. Larvae were genetically identified with a multilocus approach as A. simplex ( s.s. ). Histochemical, immunohistochemical and ultrastructural observations were conducted on 30 M. poutassou specimens. Gonads, pyloric caeca and flesh harboured encapsulated larvae of A. simplex ( s.s. ) but no intense host reaction was encountered around the parasite in the above organs. In the liver, the most infected organ, the larvae co-occurred with the coccidian Goussia sp. Within the granuloma around the A. simplex ( s.s. ) larvae, two concentric layers were recognized, an inner mostly comprising electron-dense epithelioid cells and an outer layer made of less electron-dense epithelioid cells. Macrophages and macrophage aggregates (MAs) were abundant out of the granulomas, scattered in parenchyma, and inside the MAs, the presence of engulfed Goussia sp. was frequent. In liver tissue co-infected with Goussia sp. and A. simplex ( s.s. ), hepatocytes showed cytoplasmic rarefaction and acute cell swelling. Results suggest that the host-induced encapsulation of A. simplex ( s.s. ) larvae is a strategic compromise to minimize collateral tissue damage around the larval infection sites, to facilitate the survival of both parasite and host.